Provisioning and Cultural Services of Restored Ecosystem in Mount Kelud After 2014 Eruption - Ardina Tanjungsari; Luchman Hakim; Catur Retnaningdyah (Indonesian Journal of Environment and Sustainable Development, 2018)
Mount Kelud eruption in 2014 was recorded as the largest eruption in the history of Mount Kelud volcanic activity. The ecosystem restoration was implemented after eruption, and so far there are few studies regarding the value of the restored area, especially in the perspective of ecosystem services values. The objectives of this study were to evaluate the ecosystem services of restored area of Mt. Kelud after three year or eruption restoration program and develop appropriate restoration strategies based on the potentiality of its cultural services. Field survey was done at the restored area after mountain eruption in 2014. The location of Mt. Kelud is administratively located at Sugihwaras Village, Ngancar District, Kediri Regency, East Java. Ecosystem service was observed following Wunder and Thorsen ecosystem service classification. Interviews with informant was performed to generate data regarding the socio-ecological aspect of restoration program and determining the ecosystem services in the perspectives of local community. In order to describe the strategy for the development of nature-based tourism as one of the important cultural services in Mt. Kelud, a SWOT analysis was performed to evaluate the possibility strategy to developed nature-based tourism in restored area. Results of this study shows that after three years of restoration, two ecosystem services were observed in Mt. Kelud, the provisioning services and cultural services. These services were identified contribute to the local community through numerous forestry program and nature-based tourism activity. The potentiality of nature based tourism development in restored area depend on the ability to drawn restoration planning which is combined by sustainable recreation activity in restoration area.Keywords: Ecosystem services, Mountain Kelud, Mountain restoration, Mountain tourism